The influence of the smartphone user’s characteristics on the intention to use of m-health - Zuhal Hussein, Zuhal; Harun, Amran; Oon, Siti Waringin (DergiPark Akademik, 2016)
M-Health is a new technology which has evolved from the unprecedented spread of mobile technologies as well as advancements in their innovative application to address health priorities. Implementing mobile technology will promote healthcare services with regards to improvement in accessibility, effectiveness, and affordability. This technology is growing rapidly since it was introduced 20 years ago. There are over 7 billion mobile cellular subscribers worldwide and 1.48 million of these are Malaysian subscribers. The penetration of mobile phone networks in Malaysia has transformed the way health services and information are accessed, delivered, and managed. While this technology is still new, there is a scarcity of research material on the acceptance of M-Health in Malaysia.This study proposes and empirically tests the smartphone users’ characteristics such as users’ sex, age, level of education and health condition as important factors that affected the adoption of new M-Health systems. To fill in this gap, this study is to explore the relationship between the smartphone users’ characteristics, with the intention of using M-Health. This study has recruited 80 smartphone users in Sarawak through random sampling using a survey method. Data were analysed using Statistical Package of Social Sciences (SPSS) Version 17, and various statistical techniques were used such as descriptive analysis, T-Test and One–way ANOVA. Findings indicate that there are no significant differences between sex, age, level of education and having health problems were there was an intention to use M-Health. In conclusion, the acceptance of M-Health is not dependent on the users’ characteristics, hence it is important for health technologies and mobile companies to handle different aspects in the planning and development of healthcare applications for a market strategy.